Overcoming therapeutic resistance to platinum-based drugs by targeting Epithelial–Mesenchymal transition - Duan, Xirui; Luo, Maochao; Li, Jian; Shen, Zhisen; Xie, Ke (Frontiers in Oncology, 2022)
Platinum-based drugs (PBDs), including cisplatin, carboplatin, and oxaliplatin, have been widely used as mainstay treatments for various types of cancer in clinical practice. Although there exists firm evidence of notable contributions made by PBDs to the management of cancers, the acquisition of resistance to these agents is still a major challenge to cure efforts. The introduction of the epithelial-mesenchymal transition (EMT) concept, a critical process during embryonic morphogenesis and carcinoma progression, has offered a mechanical explanation for the phenotypic switch of cancer cells upon PBD exposure. Accumulating evidence has suggested that carcinoma cells can enter a resistant state via the induction of EMT. In this review, we aim to discuss the underlying mechanisms of PBD-induced EMT and the current understanding of its role in cancer drug resistance, with an ongoing emphasis on how this novel knowledge can be taken advantage of to overcome PBD resistance via EMT-targeted compounds, especially those under clinical trials.